An Inner City in Decline: St. John's, Newfoundland - Shrimpton, Mark; Sharpe, Christopher (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
The inner core of St. John's suffered a higher rate of population loss between 1971 and 1976 than that of any other Canadian metropolitan area. In part the depopulation resulted from lower levels of fertility, a phenomenon affecting all of North America. Population loss, however, has also been influenced by the deterioration of the commercial and residential environment of the core, and by the continued development of housing and commercial space in the suburbs. Some of the major causes of inner city deterioration are discussed, including the lack of development control on the part of the municipal government. The impact, both beneficial and harmful, of various federal government policies is also examined.